Dual-Target Compounds against Type 2 Diabetes Mellitus: Proof of Concept for Sodium Dependent Glucose Transporter (SGLT) and Glycogen Phosphorylase (GP) Inhibitors - Ádám Sipos; Eszter Szennyes; Nikolett Éva Hajnal; Sándor Kun; Katalin E. Szabó; Karen Uray; László Somsák; Tibor Docsa; Éva Bokor (MDPI AG, 2021)
A current trend in the quest for new therapies for complex, multifactorial diseases, such as diabetes mellitus (DM), is to find dual or even multi-target inhibitors. In DM, the sodium dependent glucose cotransporter 2 (SGLT2) in the kidneys and the glycogen phosphorylase (GP) in the liver are validated targets. Several (β-D-glucopyranosylaryl)methyl (het)arene type compounds, called gliflozins, are marketed drugs that target SGLT2. For GP, low nanomolar glucose analogue inhibitors exist. The purpose of this study was to identify dual acting compounds which inhibit both SGLTs and GP. To this end, we have extended the structure-activity relationships of SGLT2 and GP inhibitors to scarcely known (C-β-D-glucopyranosylhetaryl)methyl arene type compounds and studied several (C-β-D-glucopyranosylhetaryl)arene type GP inhibitors against SGLT. New compounds, such as 5-arylmethyl-3-(β-D-glucopyranosyl)-1,2,4-oxadiazoles, 5-arylmethyl-2-(β-D-glucopyranosyl)-1,3,4-oxadiazoles, 4-arylmethyl-2-(β-D-glucopyranosyl)pyrimidines and 4(5)-benzyl-2-(β-D-glucopyranosyl)imidazole were prepared by adapting our previous synthetic methods. None of the studied compounds exhibited cytotoxicity and all of them were assayed for their SGLT1 and 2 inhibitory potentials in a SGLT-overexpressing TSA201 cell system. GP inhibition was also determined by known methods. Several newly synthesized (C-β-D-glucopyranosylhetaryl)methyl arene derivatives had low micromolar SGLT2 inhibitory activity; however, none of these compounds inhibited GP. On the other hand, several (C-β-D-glucopyranosylhetaryl)arene type GP inhibitor compounds with low micromolar efficacy against SGLT2 were identified. The best dual inhibitor, 2-(β-D-glucopyranosyl)-4(5)-(2-naphthyl)-imidazole, had a Ki of 31 nM for GP and IC50 of 3.5 μM for SGLT2. This first example of an SGLT-GP dual inhibitor can prospectively be developed into even more efficient dual-target compounds with potential applications in future antidiabetic therapy.